Perencanaan Kebutuhan Tempat Tidur Per Bangsal Berdasarkan Standar Depkes di RSUD Dr. Moewardi Tahun 2020-2022 - Yeni Tri Utami; Nopita Cahyaningrum; Ihda Zahrotul Jannah (Jurnal Infokes, 2021)
RSUD Dr. Moewardi is a health service institution that provides inpatient services. Based on thepreliminary survey the number of patients has decreased, but there are still queues in some wards, this isnot in line with the data reported. So that there needs to be an evaluation for planning the need for a bedso as to achieve efficiency based on Department of health standards.This type of research is descriptive with a retrospective approach. The population in this study is thedaily census recapitulation report of inpatients per ward per month 2017-2019. The sample uses a totalsampling technique. The research method used was observation and interviews.There are still many BOR values in 2017-2019 that are not yet ideal. Wards with an increase in thenumber of treatment days in 2020-2022 are in Anggrek I, Flamboyan 6, Flamboyan 7, Flamboyan 8,Flamboyan 9, and Flamboyan 10 wards, while other wards have decreased. The wards that experiencedadditional needs for beds in 2020-2022 are Flamboyan 6, Flamboyan 7, Flamboyan 8, Flamboyan 9, andFlamboyan 10 wards.The conclusion of this study is that there are still many wards that do not meet the standard ofefficiency with the needs of the available beds. Suggestions should be made to reallocate the bed from theward which needs to be reduced so that it can be used in an additional ward, combining the ward with thesame non-infectious case which still has a low BOR value.